GRP-007 A Retrospective Survey of Patient Outcomes After Switching Intravenous Immunoglobulin. (12th March 2013) - Kent, J
Abstract : Background: The market place for human immunoglobulins is constantly evolving and reacting to instability of supply of the raw material. This has meant new products emerging as well as old products being replaced or withdrawn. The NHS 'Demand Management Plan' has stabilised the UK market and helped to ensure adequate supplies. This plan also included a national contracting process and this has led to more cost-effective products becoming available. These issues have led to two occasions when a complete product switch of the IVIg patient population was undertaken at Southend Hospital NHS Trust. Purpose: To assess the level of significant adverse effects, resulting in product discontinuation, seen during two IVIg switches in 2009 and 2011. Materials and Methods: The hospital pharmacy system was used to identify all IVIg patients. Patient notes were requested for review. Each patient's entry on the UK IVIg database was reviewed. Results: 68 patients completed a total of 98 switches. 2 patients were unable to continue with the alternative IVIg product. Both were receiving monthly IVIg infusions for multiple myeloma. Both experienced headaches and flu-like symptoms post-IVIg infusion after being switched to Octagam 10% and were subsequently returned to their previous product, Intratect. Conclusions: The switching of IVIg products is typically not encouraged. However there is a very little recently published literature that discusses the problems encountered when switching these products. The quality and relevance of what is available is variable and often relates to non-UK products. This retrospective survey indicates that comprehensive IVIg switch programmes can be undertaken with a low level of patient disruption. No conflict of interest.